Dannelse og ingeniørfaglighed - Christensen, Steen Hyldgaard; Buch, Anders (Tidsskrift for Professionsstudier, 2022)
International interdisciplinary research on engineering education and practice (Christensen et al., 2007, 2009, 2019, and 2022 forthcoming) points to the fact, that the engineer’s understanding of the ‘social’ is underprioritized and discursively enacted as soft versus hard technical disciplines. As a result, it has often contributed to a cultural impoverishment of our lifeworld. Hence there is a need for a Bildung perspective in engineering degree programs. A perspective taking its point of departure in the democratic, cultural, and human challenges of society. The discourse on Bildung has primarily taken place in relation to the pedagogical professions, whereas the engineering profession has often been overlooked. In this contribution we make up for this by considering a contribution with potential for supplying a concept of Bildung suitable for the engineering profession and engineering degree programs. The article brings forth the social and ethical responsibility embedded in engineering work in democratic societies and calls to mind John Dewey´s democratic understanding of Bildung (Dewey, 2011 [1916]). The article projects, how this understanding of Bildung might offer an opportunity for rethinking engineering and engineering activity capable of contributing to democratic and responsible resolutions of societal challenges.